COVID-19 impact on socioeconomic in the hospitality industry - Che Ahmat, Nur Hidayah; Rahamat, Syafiqah; Arendt, Susan W. (Global Academy of Training and Research, 2021)
Objective - This paper provides an overview of the COVID-19 crisis and the impact of restriction orders on the hospitality industry in Malaysia. The authors review existing studies related to COVID-19 and the hospitality industry while focusing on challenges faced by the hospitality industry in Malaysia. Then, the authors summarize the socioeconomic impact of COVID-19 on the hospitality industry. Methodology/Technique - This paper examines previous COVID-19 related research published in top-tier hospitality journals during the pandemic period of December 2019 to September 2021. Research studies were categorized by topic area, hospitality industry segment, and research methods used. Additionally, the authors explored the socioeconomic impact of the COVID-19 on hospitality industry using content analysis. Findings - Most articles focused on administration/strategy, marketing, and human resources. The findings showed some potential shifts in the methods used by researchers who published during the pandemic. The findings revealed that the pandemic has negatively impacted the socioeconomic situation in many countries. Employment, public safety, finance, and physical and mental health are among the pressing issues highlighted by most researchers. Based on the findings, the authors provide insights and recommendations for further research. Novelty - This paper represents a pioneering attempt to identify a potentially unexplored area of research related to COVID-19, particularly in Malaysia. The novelty of this paper is that the authors provide substantial discussion on the socioeconomic impact of the COVID-19 on various countries' hospitality and tourism industries.